Spaces of (dis)location - Hamilton, Rachael; Macleod, Allison; Munro, Jenny (Language and Literature Ser., 2013)
Spaces of (Dis)location was a two-day interdisciplinary and international conference which took place on 24-25 May, 2012, at the University of Glasgow, UK, and was funded by the Graduate School of the University of Glasgow's College of Arts. Over the two days of the conference, around 60 papers were delivered, and this volume aims to showcase some of the most engaging and innovative research which was presented. As national and cultural boundaries are blurred in our increasingly global socie ...